2016
DOI: 10.1155/2016/2395634
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nox2 and p22phox in Persistent Postoperative Hypertension in Aldosterone-Producing Adenoma Patients after Adrenalectomy

Abstract: Adrenal aldosterone-producing adenoma (APA), producing the salt-retaining hormone aldosterone, commonly causes secondary hypertension, which often persists after unilateral adrenalectomy. Although persistent hypertension was correlated with residual hormone aldosterone, the in vivo mechanism remains unclear. NADPH oxidase is the critical cause of aldosterone synthesis in vitro. Nox2 and p22phox comprise the NADPH oxidase catalytic core, serving to initiate a reactive oxygen species (ROS) cascade that may parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Consistent with previous studies (4,23), our study showed that compared to matched EH controls, PA patients exhibited more renal damage indicated by reduced eGFR and greater prevalence of microalbuminuria, as well as more cardiac damage indicated by an increased prevalence of LVH. On the one hand, there is accumulating evidence including our previous researches, which support that many detrimental effects of aldosterone excess are involved in causing pre-clinical TOD in the PA patients; they include inflammation, oxidative stress, endothelial dysfunctions, and vascular calcification (7,(24)(25)(26)(27). On the other hand, a majority of patients with MetS, a cluster of risk factors, tend to develop structural and functional abnormalities of target organs, which precede cardiovascular complications (28,29).…”
Section: Discussionmentioning
confidence: 92%
“…Consistent with previous studies (4,23), our study showed that compared to matched EH controls, PA patients exhibited more renal damage indicated by reduced eGFR and greater prevalence of microalbuminuria, as well as more cardiac damage indicated by an increased prevalence of LVH. On the one hand, there is accumulating evidence including our previous researches, which support that many detrimental effects of aldosterone excess are involved in causing pre-clinical TOD in the PA patients; they include inflammation, oxidative stress, endothelial dysfunctions, and vascular calcification (7,(24)(25)(26)(27). On the other hand, a majority of patients with MetS, a cluster of risk factors, tend to develop structural and functional abnormalities of target organs, which precede cardiovascular complications (28,29).…”
Section: Discussionmentioning
confidence: 92%
“…59 An involvement of this pathway is consistent with the increased levels of NOx2 and p22phox, which forms the catalytic core of NADPH, in APA patients. 60,61 While probably relevant for the pathophysiology of APA, the lack of data currently precludes use of either NRF2, or NADPH as markers of aldosterone-producing cells.…”
Section: Nuclear Factor Erythroid-derived 2 (Nrf2) and Reduced Nicotimentioning
confidence: 99%